Polymer-based biomaterials for pharmaceutical and biomedical applications: A focus on topical drug administration. (3rd April 2023) - Pires, Patrícia C.; Mascarenhas-Melo, Filipa; Pedrosa, Kelly; Lopes, Daniela; Lopes, Joana; Macário-Soares, Ana; Peixoto, Diana; Giram, Prabhanjan S.; Veiga, Francisco; Paiva-Santos, Ana Cláudia
Graphical abstract: Highlights: Natural polymer-based biomaterials are reviewed as promising delivery systems. Bioactive properties of natural polymers favor their use in pharmaceutical applications. The efficacy of natural polymer-based biomaterials in topical drug delivery has been elucidated. Natural polymer-based biomaterials for the management of skin affections have a promising application potential. Abstract: The increasing emergence of skin diseases and the difficulty in treating damaged skin using conventional therapies have been calling for the development of novel drug delivery systems towards an effective topical drug administration. Drug delivery systems are able to produce these results by means of improved drug delivery features, including controlled drug release, increased drug skin permeation and retention, and decreased systemic adverse effects. Natural polymers have proved to be good excipients for incorporation in hybrid systems (nanocarriers dispersed in a semisolid base) for the management of skin affections. In addition to being biocompatible, biodegradable, economic, easily available and based on renewable resources, natural polymers also have intrinsic bioactive properties that greatly enhance their applicability in drug delivery systems. Examples of such are chitosan, alginate, agarose, starch, hyaluronic acid, silk fibroin, collagen, gelatin, and many others. These polymers also play a crucial role in the preparation of polymeric nanoparticles, that increase skin penetration, but also in the preparation of semisolid bases for cutaneous application, which improves the viscosity of the formulations and, consequently, provides a suitable topical application for the management of skin diseases. This review aims to present and discuss some of the latest drug delivery system technologies using natural polymers and analyze the respective in vitro, ex vivo and in vivo experiments to improve topical treatments. In addition, the present manuscript highlights the advantages and effective therapeutic capabilities of the use of nanoparticles composed of different biopolymers for various skin conditions, such as burns, wound healing, prevention of scar formation during wound healing, treatment of dermal infections, and also pathologies such as atopic dermatitis.